Pengaruh Brand Image dan Service Quality Terhadap Keputusan Konsumen dalam Menggunakan Jasa Pengiriman PT JMS Logistics Kota Palembang - Febrianto, M. Asyraf Rally; Roswaty; Kurniawan DP, Muhammad (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
This study aims to determine the effect of brand image and service quality on consumer decisions in using the delivery service of PT JMS Logistics Palembang City. This research uses quantitative methods. The population studied is consumers who use the delivery service of PT JMS Logistics Palembang City. The sampling technique used was accidental sampling technique with a total of 55 respondents. Data analysis techniques used are validity test, reliability test, classic assumption test, multiple linear analysis, t test, F test and coefficient of determination using SPSS version 24. The results of the research and hypotheses show that: 1) brand image partially has a positive effect and significant to consumer decisions with a sig. 0.032 and tcount = 2.205, 2) service quality partially has a positive and significant effect on consumer decisions with a sig value. 0.000 and tcount = 6.035, 3) brand image and service quality simultaneously have a positive and significant effect on consumer decisions with a sig. 0.000 and Fcount = 26.658, 4) the coefficient of determination (R²) indicates that the brand image and service quality variables can explain the consumer decision variable by 50.6%, while the remaining 49.4% is explained or influenced by other variables outside the study.